(untitled) (Transport systems and technologies, 2023)
The correct loading of bulk carriers is essential for their maritime safety. Inadequate loading can lead to various risks, including compromised hull strength, reduced stability and violation of the vessel’s seaworthiness. Existing shipboard instruments do not allow for timely planning and real-time control of loading operations, which can lead to potential risks. The high intensity of loading operations at dry bulk terminals exacerbates the problem, as there is often insufficient time to adequately prepare and verify loading plans, increasing the risk of overloading cargo holds. To address this problem, the article proposes the development of new methods for bulk carriers cargo operations planning. These methods would optimise the distribution of bulk cargo, taking into account factors such as port facilities, ship design and nautical restrictions of the planned voyage. The aim is to formalise cargo operations in terms of a mathematical model of the vessel and to establish functional relationships between parameters that affect the seaworthiness of the vessel. By analysing the relationships between different parameters, the researchers aim to determine the best strategy for cargo operations that will ensure the continuous seaworthiness of the bulk carriers. This approach would help to improve bulk carrier’s safety and reduce the risks associated with incorrect loading. The development of such methods is seen as a promising area of scientific research that can enhance the safety of those vessels. By determining the best strategy for cargo operations based on the criterion of continuous seaworthiness, it aims to prevent the deterioration of the vessel’s structural integrity and ensure that the vessel remains in a seaworthy condition throughout the loading process. The article emphasizes the need for scientific research in this area to enhance the safety of bulk carriers and proposes the development of new methods based on mathematical modeling to optimize cargo operations and maintain the vessel’s seaworthiness throughout the process.